Biological attributes of cabbage butterfly, Pieris brassicae(L.) and its natural parasitism in mid-altitudes of Meghalaya - Lytan, Damitre; D.M.Firake; D.M.Firake (Umiam : CPGS, CAU, 2012)
Cabbage butterfly, Pieris brassicae (L.) is the most destructive pest of cruciferous crops of the hilly region. Several aspects on management and biology of P. brassicae (L.) have been extensively studied in different parts of the world,including NEH region. However, many ecological and quality control aspects in relation to its biological control have been often ignored, which have immense significance for their eco-friendly management. Therefore, studies on biological attributes of cabbage butterfly, P. brassicae (L.) and its natural parasitism were undertaken at Division of Entomology, ICAR Research Complex for NEH Region, Umiam. The experiments were conducted both in the natural conditions as well as in the laboratory during 2010-2011. The experimental farms of other divisions were also been utilized for natural parasitism study. Overall results indicated that, cruciferous ecosystems of Meghalaya harbor several potential natural enemies during different growth stages of crops. Amongst, coccinellids, syrphids, ichneumonids, chalcids and tachinids were common natural enemies observed during different growth stages. Additionally, four species of predatory spiders were also observed throughout the season. Behavioural studies on butterfly showed, comparatively more egg masses on knol-khol, but the number of eggs per mass was found to be higher on cabbage, suggesting its host preference towards cabbage than other cole crops. Furthermore, preference of lower leaf surface for oviposition as well as pupation was significantly higher on cabbage as compared to other cole crops. Development time and weight of the P. brassicae (L.) was higher on cauliflower under both field and laboratory conditions. However, butterfly took comparatively longer time to develop under laboratory conditions. Interestingly, development time of the butterfly had shown inverse relations to their weight. Parasitism of P. brassicae (L.) by Hyposoter ebeninus (Grav.) was found to be higher on knol-khol under field conditions. Interestingly, weight of parasitized caterpillar was significantly higher on cabbage. Similarly, weight of cocoon was also more on cabbage and knol-khol reared caterpillars. H. ebeninus (L.) was recorded as a predominant larval parasitoid and its activity was found to be highest during the end of February. Moreover, activity of Cotesia glomerata (L.) and Pteromalus puparum (L.) was reasonably higher during March. Temperature, wind speed and sunshine showed negative correlation with parasitism by H. ebeninus (Grav.) and significant positive correlation with parasitism by C. glomerata (L.) and P. puparum (L.). Furthermore, relative humidity showed negative correlation with parasitism by H. ebeninus (Grav.) and C. glomerata (L.). Overall studies can be concluded that, cruciferous ecosystem harbor several prospective natural enemies in mid altitude hills of Meghalaya. Moreover, different host plants of P. brassicae larvae have strong influence on parasitization potential as well as body weight of koinobiont parasitoid. Endolarval parasitoid, H. ebeninus (Grav.) is the most dominant larval parasitoid of P. brassicae (L.) in the region. Therefore, we have tremendous scope for their conservation and further utilization under field conditions.
Keywords: Cabbage butterfly -- Natural parasitism -- Meghalaya; Pieris brassicae(L.)